Students' Ability to Solve Story Problems on Systems of Linear Equations Using John Dewey's Approach - Suryanti, Suryanti; Solikhah, Bety Maratus; Suliana, Riki; Pramesti, Cicik; Sari, Ayu Silvi Lisvian (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
Students can study everyday mathematics with a story problem. Through this problem, students gain critical thinking experience in solving problems. The ability of students to solve problems through John Dewey's approach is also seen to deepen students' mathematical concepts in three-variable linear equation systems. Problem solving with John Dewey's approach consists of five stages. This method of research uses a qualitative descriptive approach with three persons as the subject of the research, with good, sufficient, and less as the categories of ability. The results of the research showed the subject's ability to solve a story problem with the John Dewey approach. Four given questions showed that the subject with a category of good ability can solve two problems with clear mathematical concepts. Whereas the student with sufficient ability can only solve one problem with an obvious mathematical concept, However, the subject with less ability is only able to solve a problem until the stage of inventorying several solutions, which is the third stage of problem solving with the approach of John Dewey.